ER nurses [compact disc, unabridged] : true stories from America's greatest unsung heroes - Patterson, James, 1947-; Eversmann, Matt (Hachette Audio, 2021)
These everyday American heroes serve our neighbors, our friends, our families. Their stories, their lives, are extraordinary and unforgettable. Around the clock and across the country, ER nurses are the heart and soul of our city, town, and county hospitals. They make a difference every day, to everyone they touch. E.R. Nurses puts names and faces to these men and women who are there for us whenever we need them, who fight for our lives and never give up.